How can African agriculture adapt to climate change: Vulnerability and the impact of climate change in South Africa's Limpopo River Basin - Shewmake, Sharon (International Food Policy Research Institute, 2008)
With likely long-term changes in rainfall patterns and shifting temperature zones, climate change is expected to increase the frequency of climate-related shocks, such as floods and droughts in Sub-Saharan Africa. For farm households, an increase in the frequency of climate-related income shocks could lead not only to lower expected income, but also to higher income variance, which in turn can cause them to pursue costly risk-coping strategies and to fall below poverty trap thresholds. For this reason, it is important to understand how a changing distribution of risk will lead to increased vulnerability, not just decreased expected income. This brief is based on a paper that uses farm households' responses to climate-related shocks in South Africa's Limpopo River Basin to gauge how farmers are likely to respond to future climate change shocks. The increased frequency and severity of droughts associated with global warming may induce farmers to change their behavior to reduce their risk of negative impacts from future climaterelated shocks. While it is difficult to predict farmers' behavior and how it will affect welfare, coping strategies used in response to shocks today can be used to predict whether and how rural South Africans will cope in the future. The study examines household responses to droughts in 2005 and household vulnerability to future climate change by assessing their probability of falling below an income threshold as a result of future climate-related shocks. Assessing household vulnerability is important because efficient social policy needs to go beyond poverty alleviation in the present to prevent poverty in the future. A poverty reduction strategy that doesnot distinguish between transient and structural poverty leads to inefficient use of resources, in that it focuses on those who are temporarily poor but may be able to escape poverty on their own, at the expense of those who have a high probability of becoming chronically poor.